2022
DOI: 10.1038/s41577-022-00694-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by endothelial cells — partnering up with the immune system?

Abstract: Blood vessel endothelial cells (ECs) have long been known to modulate inflammation by regulating immune cell trafficking, activation status and function. However, whether the heterogeneous EC populations in various tissues and organs differ in their immunomodulatory capacity has received insufficient attention, certainly with regard to considering them for alternative immunotherapy. Recent single-cell studies have identified specific EC subtypes that express gene signatures indicative of phagocytosis or scaven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(173 citation statements)
references
References 200 publications
(261 reference statements)
2
128
0
Order By: Relevance
“…However, numerous studies have shown that these cells may play a more direct role in tolerance, immune surveillance (scavenging), active phagocytosis, immune cell recruitment from the periphery, and antigen presentation to conventional (CD4/CD8) and unconventional (iNKT) T cells. Collectively, these EC subsets are referred to as immunomodulatory endothelial cells (IMECs), and their numerous unique functions have been detailed elsewhere ( Amersfoort et al., 2022 ). However, evidence for detrimental functions during antiviral response have also been uncovered.…”
Section: Innate Respiratory Response: Structural and Non-circulating ...mentioning
confidence: 99%
“…However, numerous studies have shown that these cells may play a more direct role in tolerance, immune surveillance (scavenging), active phagocytosis, immune cell recruitment from the periphery, and antigen presentation to conventional (CD4/CD8) and unconventional (iNKT) T cells. Collectively, these EC subsets are referred to as immunomodulatory endothelial cells (IMECs), and their numerous unique functions have been detailed elsewhere ( Amersfoort et al., 2022 ). However, evidence for detrimental functions during antiviral response have also been uncovered.…”
Section: Innate Respiratory Response: Structural and Non-circulating ...mentioning
confidence: 99%
“…Recent interesting studies also demonstrated that ECs have many innate immune functions and express gene signatures indicative of phagocytosis or scavenging, antigen presentation, and immune cell recruitment [ 14 ]. Specifically, they have functions that macrophages express, including cytokine secretion, phagocytic function, antigen presentation, pathogen-associated molecular patterns-, and danger-associated molecular patterns-sensing, proinflammatory, immune-enhancing, anti-inflammatory, immunosuppression, migration, heterogeneity, and plasticity [ 11 ].…”
Section: Immunological Roles Of the Endotheliummentioning
confidence: 99%
“…Moreover, ECs behave as innate immune cells also in metabolic cardiovascular diseases, other sterile inflammations, and cancers. These concepts are extremely relevant in the case of chronic inflammatory states, which have a known role in cancerogenesis [ 14 ].…”
Section: Immunological Roles Of the Endotheliummentioning
confidence: 99%
See 1 more Smart Citation
“…The lymphatic vessels serve as a conduit to channel immune cells to counteract cancer cell growth [19]. Indeed, crosstalk between lymphatic and immune cells plays an important role in the uptake/migration of cells into the lymphatics [20] via LEC-generated chemokine(s) gradients [21].…”
Section: Introductionmentioning
confidence: 99%